Fatores associados à não adesão ao tratamento farmacológico em pacientes que hospitalizaram por condições cardiovasculares sensíveis à atenção primária e seu impacto financeiro para o sistema de saúde - Schneider, Ana Paula Helfer (Universidade do Vale do Rio dos Sinos, 2017)
Cardiovascular diseases (CVD) are among the leading causes of death in Brazil. They account for about 20% of all deaths in individuals over 30 years. Medication Adherence determines the success or otherwise of a treatment where the patient needs control of his or her health status. The main factors that may interfere in adherence, described by the World Health Organization (WHO), are socioeconomic conditions, personal characteristics, aspects related to the treatment and/or illness, the professional team involved and the health system to which it belongs. Studies demonstrate average percentages of compliance with pharmacological treatment of about 50 to 79%. This thesis aimed to evaluate factors associated with nonadherence to medications in adults with CVD. Two articles with different objectives emerged from this thesis. The first one aims to summarize the evidence regarding the relationship between characteristics of pharmacotherapy and nonadherence to medication in the CVD population through a systematic review with meta-analysis. Several characteristics of pharmacotherapy were examined and two associated modifiable factors resulted; (i) a 24% decrease in the risk of non-adherence among CVD patients who have insurance or another program that assists with medication and (ii) a 38% increase in the risk of non-adherence among CVD patients who take their medication in two or more daily doses. Another article aimed to evaluate the association between complexity of the therapeutic regimen and low adherence medications in adults hospitalized for Cardiovascular Conditions Sensitive to Primary Care (CCSAP) where there was an inverse association between the complexity of the therapeutic regimen and adherence to medications, with a 22% higher probability of low adherence in patients who used highly complex therapeutic regimens, even after adjustment for potential confounders (RP = 1.22, 95% CI 1.01-1.47). In the model adjusted for autonomy in the administration and organization of medicines, this effect loses statistical significance (RP = 1.16, 95% CI: 0.96-1.40). Thus, the adoption of strategies that promote user autonomy in the administration and organization of the therapeutic regimen are fundamental measures to increase the adherence of individuals to complex therapeutic regimens. Therefore, understanding the mechanisms underlying adherence behaviors may improve patient-specific approaches to improve adherence and this study contributes significantly to this area, pointing to modifiable factors that may improve adherence to the pharmacological treatment of adults with CVD.
Keywords: Adesão à medicação; Doenças cardiovascular; Atenção primária em saúde; Medication adherence; Cardiovascular diseases; Primary health care; ACCNPQ::Ciências da Saúde::Saúde Coletiva